PRIVILEGES ACCORDED TO THE PRINTING HOUSES IN THE GRAND DUCHYOF LITHUANIA - Kažuro, Ina (Knygotyra, 2017)
The article aims to shed light on the privileges accorded by the rulers of the Grand Duchy of Lithuania (hereinafter referred to as GDL) as a legal means of printed press regulation. It should be noted that so far, the research has mostly been focused on the privileges granted to the printing houses of the Mamoniciai and Vilnius academies. The current research, based on various studies about the privileges granted to other printing houses and new historical sources, attempts to provide a comprehensive analysis of the privilege phenomenon in its entirety, by examining the dynamics of granting privileges, privilege providers and recipients, types of privileges, sanctions imposed and the languages in which printing was allowed. It has been established that during the period of 1569–1793, the 37 privileges by rulers were granted to GDL printing houses. In the second half of the 16th century, the GDL rulers accorded 6 privileges, in the 17th century – 8, and in the 18th century – 22 privileges, respectively. The greatest number of the privileges was granted during the reign of Augustus III (the period of 1734–1763) and Stanislaw II Augustus (the period of 1764–1795). During the 29 years of holding the throne, Augustus III granted 10 privileges to the GDL printing houses. Stanislaw II Augustus reigned the GDL for 31 years, during which he issued 7 privileges. Among the GDL rulers were also the individuals who failed to grant a single privilege to the existing printing houses. They were John II Casimir Vasa (1648–1668), whose reign coincided with the wars waged against Moscow and Sweden and Stanisław I Leszczyński (1704–1709, 1733–1734). On the grounds of the intended business purposes, the privileges granted to the GDL printing houses can be classified as publishing privileges (in total 13 privileges, accounting for 35%), the privileges to establish a printing house (in total 9 privileges, accounting for 24%), confirming privileges (in total 11 privileges, accounting for 30%) and miscellaneous privileges (in total 4 privileges). In the 16th and the first half of the 17th century, the privileges accorded by the rulers were not very widespread, as part of the printing houses conducted their activities under the auspices of the GDL noblemen. In the 18th century, GDL saw the predominance of institutional printing house. It is only natural that such printing houses sought the privileges granted by the rulers as an important means to establish themselves in the book printing market. Among the GDL institutions having a printing house of its own, was a higher education institution (Vilnius Jesuit Academy), religious organizations of city-dwellers (so-called fraternities) and monasteries (Catholic, Orthodox and Uniate). The largest number of privileges was granted to the printing house of the Vilnius Jesuit Academy (in total 13 privileges), whereas the printing houses of other GDL institutions (brotherhoods of city-dwellers as well as Catholic, Orthodox and Uniate monasteries) were usually accorded one, two or three privileges. The analysis of thirteen privileges granted to the GDL printing houses revealed that they included penalties foreseen for violating publishing rights. The greatest sanction ever in the history of GDL printing – 5000 florins (Italian coins)– was in 1588 imposed on the GDL nobleman Kazimierz Leon Sapieha for violating the privilege to publish the Lithuanian Statute. In the history of GDL printing, one case should be particularly highlighted, namely, when a large fine was imposed not for illegal reproduction but for resisting the failing to comply with the purpose of the privilege – to establish a printing house. More specifically, the 1701 privilege granted by Augustus II foresaw a fine of 1000 kapa (medieval unit of measurement used in the 15–18th century GDL) imposed on anybody for hindering the Mogilev Orthodox brotherhood in their attempt to establish a printing house. The privileges accorded by GDL rulers gave permission to publish books not only in the official literary languages – Polish and Latin – but also in the languages of ethnoconfessional communities such as Ruthenian, Lithuanian and Jewish. Even though in principle, the privileges granted by GDL rulers did reflect benevolence for printing books in the languages of other GL confessions and cultures, the monopoly of the Vilnius Jesuit Academy hindered the development of other printing houses.